Cost-effective solution to water scarcity in dryland environments using - Ezugwu, Charles; Omunakwe, Okechukwu; Onyekweredike, Kelechi; Moluno, Anthony; Ezugwu, Chisom; Wokoma, Innocent; Akpan, Paul; Anyaeche, Solomon; Oloyedec, Amodu (Penerbit Universiti Kebangsaan Malaysia, 2023)
Drylands are homes to many peoples of the world where frequent severe droughts are experienced, and dwellers suffering severe water shortages. Water scarcity in these environments is at alarming rate but can be alleviated by building rainwater collecting structures using sand dams. These mitigation measures are built across ephemeral sand rivers and used to store and provide clean water in these environments. The procedure for this work involves presentation of the principles and functionality of sand dams, sand dam technology, the sedimentation process, financing and future plans. The application of sand dam technology provides water solution in these communities without interruption even during periods of droughts. The challenge is that most communities with potentials for sand dams lack the resources to implement it. It is recommended that self-help group (SHG) committees be formed in these areas to relieve these people of acute water stress. Structure for monitoring and maintenance of the facility should be packaged for optimal performance and sustainability. Before use, the water should be examined, and treated where pollutants are above tolerable levels. The main finding is that some places with sand dam potentials do not have them, either due to lack of awareness or resources. A comprehensive source of funding sand dam projects, a major contribution of this work is novel, being not found in related literatures. Future plan is to work on improving the technology and incorporating waste management in the system for a sustainable environment.